Realm of shadows [videorecording (DVD)] - Drain, Jimmy; Todd, Tony, 1952-; Wells, Vernon, 1945-; Mayhew, Lauren (Safier Entertainment, 2025)
Enter a world of mystery, possession and shadows in an anthology of short horror themed tales woven into a full length feature presentation. Even the most shocking stories are based on true events. Starring horror legend Tony Todd.